Qualitative Review On Emotions in Workplace: A New Challenge for Managers: Life Sciences - Ramachandran, Divya; Sudish, R. C; Sanjeev Bansal, Prof. (Dr.) (International Journal of Life Science and Pharma Research, 2023)
This review focuses on Workplace emotions, a hot management topic today. A full understanding of the role of emotions in organizations requires focusing on how one employee’s emotions affect others’ emotions, knowledge, attitudes, and behaviors. Individuals bring their affective states, characteristics, and emotional "buttons" to work; leaders try to create passion and enthusiasm for the organization and its well-being; groups talk about Esprit de corps; and organizational consultants aim to increase job satisfaction, commitment, trust, and loyalty. Organizational members rarely do their jobs objectively, based on cold, cognitive calculation, and work experiences include a series of work events that can be pleasant and refreshing or stressful and frustrating. Without a doubt, emotions are an integral part of the workplace. We advertise emotions as social EASI’s theory that emotional expressions affect relationships and trigger affective reactions and/or reasoning processes in objects according to the object information processing and perceived appropriateness of emotional expression. We review evidence from four areas of organizational behavior: customer service, group decision, negotiation, and lead & Multilevel model of emotions: (a) within-person, (b) between-person (personality; attitudes), (c) interpersonal behaviors (perception & communication), (d) group level (leadership & teams), and (e) organizational level (culture and climate). We conclude that the study of emotions in organizations has provided new and important insights into the behavior of people in organizations, and we advise managers on how to create and maintain a positive emotional climate in their organizations.